Promoting the signal reliability of non-invasive biosensors via a N-doped graphene quantum dot modified Prussian blue analogue protective layer for glucose monitoring - Chiu, Yi-Hao; Rinawati, Mia; Chang, Ling-Yu; Aulia, Sofiannisa; Li, Chieh; Shi, Ping-Chen; Chen, Kuan-Jung; Huang, Wei-Hsiang; Mizuguchi, Hitoshi; Yeh, Min-Hsin (Journal of materials chemistry. B, Materials for biology and medicine, 2025)
Precise and reliable wearable biosensors are essential for diabetes tracking, enhancing result accuracy for patients. Prussian blue (PB) has been the subject of numerous studies in biosensor development due to its high efficiency in hydrogen peroxide reduction. However, PB's limited stability, especially in neutral pH environments, constrains its practical application. A promising approach is to combine PB with its analogues (PBA), offering a protective layer over PB, though at the cost of reduced sensitivity due to blocked active sites. In a pioneering way, this study incorporates N-doped graphene quantum dots (NGQDs) into the protective layer of PBA to address these issues, in conjunction with a PB sensing layer, to develop a wearable biosensor that possesses exceptional stability and accuracy in detection. The NGQDs facilitated the surface reconstruction of PBA driven by a strong electrostatic interaction mechanism, which can notably increase its hydrophilicity for enabling improved H 2 O 2 transport. Through these sequential methods, the surface properties of PBA were successfully improved, resulting in a substantial rise in the overall sensor sensitivity of 221.29 ± 1.77 μA mM −1 cm −2 for H 2 O 2 detection, close to the pristine PB one (247.87 ± 5.35 μA mM −1 cm −2 ). Furthermore, the glucose detection sensitivity was significantly enhanced by the immobilization of glucose oxidase (GOx) on the electrode (90.49 ± 1.08 μA mM −1 cm −2 ). In a sequence, this nanomaterial demonstrated outstanding stability with a current density retention rate of 87.37% over long-term operation at a specific concentration, and the sensitivity remained at 88.17% under repeated use. Therefore, our NGQDs/PBA/PB nanocomposite offers a durable, high-performance solution for non-invasive glucose monitoring in human sweat, advancing the development of next-generation wearable biosensors for continuous diabetes management.